2021
DOI: 10.1039/d1fo00586c
|View full text |Cite
|
Sign up to set email alerts
|

Royal jelly from different floral sources possesses distinct wound-healing mechanisms and ingredient profiles

Abstract: In recent years, population aging together with the increased prevalence of diabetes and obesity, are fuelling a surge in the instances of cutaneous non-healing wounds. Royal jelly (RJ) is a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Lack of changes in most proteins has also been shown in RJ produced under different conditions, e.g. from different floral sources ( Lin et al, 2021 ) or from pathogen-diet colonies ( Harwood et al, 2021 ). Similar to these studies, none of the MRJP members, which constitute about 90% of soluble RJ proteins ( Furusawa et al, 2008 ), was found to differ in abundance levels in our study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Lack of changes in most proteins has also been shown in RJ produced under different conditions, e.g. from different floral sources ( Lin et al, 2021 ) or from pathogen-diet colonies ( Harwood et al, 2021 ). Similar to these studies, none of the MRJP members, which constitute about 90% of soluble RJ proteins ( Furusawa et al, 2008 ), was found to differ in abundance levels in our study.…”
Section: Discussionmentioning
confidence: 92%
“…Based on ultra-high performance liquid chromatography–high-resolution mass spectrometry (UHPLC–HRMS), the two omics approaches have been applied in combination to gain a deep profiling of RJ components. Their high-throughput nature leads to identification and quantification of primary RJ components, including lipids, carbohydrates, vitamins, flavones, amino acids, and proteins ( Lin et al, 2021 ; Ma et al, 2021 , 2022b ; Milone et al, 2021 ). Quantitative differences in these substances could thus be used to assess RJ quality on a larger scale.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that it enhanced cutaneous wound healing by increasing the growth and mobility of keratinocytes, modulating the expression of aquaporin 3 (AQP3), regulating pathways involving mitogen-activated protein kinase and calcium, and mediating inflammatory responses. [ 37 ] The royal jelly used in our study was harvested in April, during the presence of spring flowers. It is thought that the reasons for the wound healing, which cannot be fully explained by histopathological results, may be attributed to these mechanisms.…”
Section: Discussionmentioning
confidence: 99%